ASME 2012 Internal Combustion Engine Division Fall Technical Conference 2012
DOI: 10.1115/icef2012-92127
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Gasoline Combustion With Diesel Micro-Pilot Injection in a Six-Cylinder Heavy Duty Engine

Abstract: This paper describes the operation of a heavy duty six-cylinder engine in a dual fuel, Low Temperature Combustion (LTC) mode with very low engine-out NOx und soot emissions according to the US EPA Tier IV final emission limits in the corresponding C1 test cycle. This operation mode makes use of a short pilot injection of diesel fuel, which is injected directly into the cylinder, to ignite a highly diluted, premixed gasoline air mixture. Multicylinder engine operation could be demonstrated over the entire engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These variations are indicative of uneven distribution of fuel across the cylinders and will be further addressed in this study. A prior study on a dual-fuel multi-cylinder engine by Bach et al 27 also identified uneven distribution of the port-injected fuel and significant cylinder imbalances due to the common inlet plenum and the pressure pulsations, especially during valve overlap. To obtain an even fuel distribution and a good mixture preparation, the authors of this prior study developed a new prototype intake manifold.…”
Section: Introductionmentioning
confidence: 92%
“…These variations are indicative of uneven distribution of fuel across the cylinders and will be further addressed in this study. A prior study on a dual-fuel multi-cylinder engine by Bach et al 27 also identified uneven distribution of the port-injected fuel and significant cylinder imbalances due to the common inlet plenum and the pressure pulsations, especially during valve overlap. To obtain an even fuel distribution and a good mixture preparation, the authors of this prior study developed a new prototype intake manifold.…”
Section: Introductionmentioning
confidence: 92%
“…The aforementioned works were developed for single fuel applications, however, when dealing with dual-fuel engines, DI injection dispersion is added to PFI variability (Bach et al, 2012;Kassa et al, 2017). As previously mentioned, the portion of LRF injected plays an important role in the combustion control and pollutant formation, a proper estimation of such variable is therefore essential.…”
Section: Introductionmentioning
confidence: 99%